The Message, Sociocultural Background, and Politics of the Religious Islamic Sermons in the Netherlands - Rr. Suhartini (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
Da‘wa is not merely concerned with theology and religion but also addresses the socio-political aspects. These aspects are highly dependent on the background of the da‘i or preacher and the public space of politics in the religion which conveys the da‘wa message. Using a qualitative method, this research focuses on three questions, which are the priority of the da‘wa message, and the suitability of the da‘i qualification in the contemporary Netherlands. The third question entails how the politics of religion support the life of Muslim migrants, and for this issue, some mosques and Muslim communities were chosen for data collection. Subsequently, this research showed that the most delivered topics of da‘wa message were about aqīdah or creed, sharī‘ah, which is the Islamic law, and then akhlāq or ethics. Also, the background of the da‘i heavily influenced the selection of the da‘wa material and involved two major streams, which were Salafi and Sunni. The da‘wa activity by the Sunni da‘is tended to be more open, compared to Salafi activities. Concerning this religion’s politics, the Dutch government launched a program, which involved the Pillarization of Islam. The program was to enable the government to maintain control over the activities of Muslim migrants and was also for the benefit of the multi-origin and multi-ethnic ones. However, this measure proved to be ineffective, and da‘wa has continued without following this pillarization program, as being a Muslim is a result of personal will, and not just because of a sermon.